Endocytosis Deficient Murine Xcl1-Fusion Vaccine Enhances Protective Antibody Responses in Mice - Gudjonsson, Arnar; Andersen, Tor Kristian; Sundvold-Gjerstad, Vibeke; Bogen, Bjarne; Fossum, Even (Frontiers in Immunology, 2019)
Targeting antigen to surface receptors on dendritic cells (DCs) can improve antibody response against subunit vaccines. We have previously observed that human XCL1-fusion vaccines target murine Xcr1+ DCs without actively inducing endocytosis of the antigen, resulting in enhanced antibody responses in mice. However, the use of foreign chemokines for targeting is undesirable when translating this observation to human or veterinary medicine due to potential cross-reactive responses against the endogenous chemokine. Here we have identified a mutant version of murine Xcl1, labeled Xcl1(Δ1) owing to removal of a conserved valine in position 1 of the mature chemokine, that retains specific binding to Xcr1+ DCs without inducing endocytosis of the receptor. DNA immunization with Xcl1(Δ1) conjugated to influenza hemagglutinin (HA) induced improved antibody responses, with higher end point titers of IgG compared to WT Xcl1-HA. The Xcl1(Δ1) fusion vaccine also resulted in an increased number of HA reactive germinal center B cells with higher avidity towards the antigen, and serum transfer experiments show that Xcl1(Δ1)-HA induced antibody responses provided better protection against influenza infection as compared to WT Xcl1-HA. In summary, our observations indicate that targeting antigen to Xcr1+ DCs in an endocytosis deficient manner enhances antibody responses. This effect was obtained by introducing a single mutation to Xcl1, suggesting our strategy may easily be translated to human or veterinary vaccine settings.